Mission La Purisima Concepcion - Kessler, Friedolin Edward:::Creator:::::::::::: (Kessler, Friedolin Edward)
Linoleum cut print of Mission La Purisima Concepcion on paper, pasted on front of greeting card. In cursive at bottom of card, Mission La Purisima Concepcion by Friedolin Kessler.